PENGARUH KUALITAS PRODUK TERHADAP VOLUME PENJUALAN PADA HOME INDUSTRI KRIPIK TEMPE “ABADI” SINGGAHAN KECAMATAN KARTOHARJO KABUPATEN MAGETAN - Izzah Yuz Rifa Widyaningrum (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
Quality is important in sales activities that need to be considered in order to meet the desires and expectations of consumers so that consumers will believe the products are made. In a study entitled "The Effect Of Quality Products At Home Sales Volume Industry Kripik Tempe" Abadi "Singgahan KartoharjoMagetan district" has a purpose: first to determine the quality of the Home Products Industry Kripik Tempe "Abadi" SinggahanKartoharjoMagetan district, both to determine the volume of sales in the Home Industries KripikTempe "Abadi" Singgahan District Kartoharjo Magetan.Based on the results of data processing and simultaneous testing on a real level (α) = 5% indicates that the quality of the product simultaneously significantly influence Sales Volume At Home IndustryKripik Tempe "abadi" Singgahan District Kartoharjo Magetan. This is evident from the value of 20.638 while the value FcountFtable 4,042. On the other hand Sighit values of 0.000 and 0.05 Sigprob. This means that the value of F count ≥ Ftabel (≥ 20.638 4.042) and Sighit ≤ Sigprob (0.05 ≤ 0.000). However, when seen from the regression equation factors positively influence the quality of the product shown in the regression equation obtained value equation Y = 50.107 + 0.494 X.